THE EFFICIENCY OF SALIVA OFFICINALIS TO REDUCE THE BIOCHEMICAL AND IMMUNOLOGICAL EFFECTS INDUCED BY MANGANESE CHLORIDE IN RATS - Ibrahim, Ihsan Raisan; Wali, Jameel Kareem (European Scientific Journal, ESJ, 2014)
This study was designed to evaluate the role of Salvia officinalis extract (sage tea) to reduce the acute effects of manganese chloride Mncl2 in some biochemical and immunological parameters. So, thirty female rats were divided into five groups, first group considered as a control group and given drinking water, the other four groups were injected intraperitoneally with Mncl2 (for ten consecutive days) while sage tea was given instead of drinking water to third, fourth and fifth group at different concentrations for ten days.at the end of the experiment, rats were sacrificed and samples of blood collected for measurment biochemical parameters that included (ALT, AST, ALP, Creatinine and Urea), as well as immunological parameters (Total and differential white blood cells count and phagocytic index).Results showed significant increase (PË‚0.05) in the levels of ALT, AST, ALP, creatinine and Urea) in group injected with Mncl2 only in comparison with control group, as well as there was significant increase in total count of cells, neutrophil, lymphocyte and phagocytic index compared with a control group.Treatment with sage tea and Mncl2 led to significant decrease (P<0.05) in levels of ALT, AST, ALP, creatinine and urea in comparison with group treated with Mncl2 only in addition to significant decrease in total white blood cells count, neutrophil and phagocytic index as well as significant increase in monocyte.Its concluded that sage tea have positive effect in reduction the effects of Mncl2.